PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) TERHADAP MOTIVASI BELAJAR DAN PEMAHAMAN SISWA DALAM MENGIMPLEMENTASIKAN NILAI-NILAI PANCASILA DI SMPN 2 TANAH MERAH BANGKALAN - Zaini, Rahmat; Muhajir; Silver, Soesiana Tri Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT This research aims to determine the effect of the Contextual Teaching Learning (CTL) learning model on students' learning motivation and understanding in implementing Pancasila values at SMPN 2 Tanah Merah Bangkalan. The research method used is quantitative using an experimental research design. This research uses motivation questionnaire instruments and comprehension tests. The population in this study was all class VII UPTD of SMP Negeri 2 Tanah Merah with a total of 90 students and a sample of class VII-A of 30 students and class VII-B of 30 students of UPTD of SMPN 2 Tanah Merah. The results of this research are: 1) Contextual Teaching Learning has an effect on the motivation of class VII students and the results are better when compared to conventional learning models with a significance value of 0.000; 2) Contextual Teaching Learning has an effect on class VII students' understanding and the results are better when compared to conventional learning models with a significance value of 0.000; 3) The Contextual Teaching Learning learning model has a more significant effect on motivation compared to the conventional model with a difference of 2.6%. And the results of student understanding with the Contextual Teaching Learning model are more significant than the conventional model with a difference of 10.2%.